2021
DOI: 10.3390/molecules27010213
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Olive Oil Screening Using Multivariate Analysis of Proton NMR Spectra

Abstract: A new NMR-based method for the discrimination of olive oils of any grade from seed oils and mixtures thereof was developed with the aim of allowing the verification of olive oil authenticity. Ten seed oils and seven monovarietal and blended extra virgin olive oils were utilized to develop a principal component analysis (PCA) based analysis of 1H NMR spectra to rapidly and accurately determine the authenticity of olive oils. Another twenty-eight olive oils were utilized to test the principal component analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…It was reported that Near Infrared (NIR) and chemometric techniques have shown 1-10% detection level of adulteration with vegetable oils only when a statistical model is used (Vanstone et al, 2018). In another study carried out by using P-NMR for principle component analysis, detection of seed oil adulteration levels was 5-20% based on type of seed oil (Ray et al, 2021). Green et al (2020) employed U-HPLC with charged aerosol detection to characterise EVOO along with potential adulterant oils based on their triacylglycerol profiles.…”
Section: Dpv Analysis Of Oil Mixturesmentioning
confidence: 99%
“…It was reported that Near Infrared (NIR) and chemometric techniques have shown 1-10% detection level of adulteration with vegetable oils only when a statistical model is used (Vanstone et al, 2018). In another study carried out by using P-NMR for principle component analysis, detection of seed oil adulteration levels was 5-20% based on type of seed oil (Ray et al, 2021). Green et al (2020) employed U-HPLC with charged aerosol detection to characterise EVOO along with potential adulterant oils based on their triacylglycerol profiles.…”
Section: Dpv Analysis Of Oil Mixturesmentioning
confidence: 99%
“…W innym badaniu analizowano dwadzieścia osiem oliw z oliwek [34]. W tym celu poddano analizie 1 H NMR dziesięć olejów z nasion oraz siedem jednogatunkowych i mieszanych oliw EVOO w celu zbadania oliw fałszowanych innymi olejami.…”
Section: Typy Zafałszowań Oliwy Z Oliwekunclassified
“…There is no literature on this specific analysis conducted with other species of tree ferns, but other studies conducted with olive oil and plant extracts highlight the importance of this analysis (Rohman et al 2020;Ray et al 2022). The ease of sample preparation, quick analysis, and easily interpretable results make this method a valuable tool for detecting fraud through substitution or dilution of plant extracts compared to other methods (Stoyanova & Brown 2001;Ray et al 2022).…”
Section: Screening By 1 H Nmr Of the Crude Leaves Extracts And Their ...mentioning
confidence: 99%